Gap Pre-pulse Inhibition of the Cortical Auditory Evoked Potentials as a Possible Objective Pinnitus Assessment Tool - shayanmehr, s.shayanmehr; Rahbar, Nariman; pourbakht, akram; sameni, seyyed jalal; mazaher yazdi, malihe (Iranian Journal of Child Neurology, 2023)
Objectives The objective assessment tests overcome the variability of subjective methods. Cortical recordings with gap pre-pulse inhibition of the acoustic startle reflex stimulus have been used as objective tinnitus assessments in humans. This study aims to investigate this possible objective tinnitus test and compare gap-induced inhibition in different stimulus parameters and brain regions. Materials & Methods Twenty People (18-50 years old) without hearing loss and tinnitus were included. The sound stimuli consisted of continuous background noise with a loud startle tone preceded by a silent gap (20 and 40 ms duration, 120 and 150 ms distance from the startle). The N1-P2 complex amplitude and topoplot maps were extracted in 27-channel cortical response recording after signal processing. Four brain regions of interest (ROI) of anterio-frontal, centro-frontal, right, and left temporal were investigated. Results The results showed that the maximum inhibition occurred in a 40 ms gap duration and 150 ms distance in all 4 ROIs. In comparing ROIs, the centro-frontal and left temporal regions revealed the most inhibition (p<0.05). The decrease in the amplitude of the N1 and P2 in that region could also be traced in the 100 and 200 ms topoplots. Conclusion Gap-induced inhibition was observed in all gap-embedded stimuli and all ROIs. However, the 40-150 mode and centro-frontal and left temporal regions had maximum inhibition in normal subjects. It provides a promising tool for objectively assessing tinnitus in humans with particular implications in children